PERLINDUNGAN KONSUMEN TERHADAPA PERBUATAN PENGALIHAN UANG KEMBALIAN DENGAN BARANG (UNDANG UNDANG TENTANG PERLINDUNGAN KONSUMEN) - Utami, Ruci; ibrahim, ukas (SCIENTIA JOURNAL, 2024)
This writing entitled "Legal Consequences of Giving Heritage When Heir Still Life Based on the Book of the Law of Civil Law " which aims to determine the legal effect when the heir to the legacy administration still live by the Book of the Law of Civil Law . In this paper , the authors use the method of writing in which the normative juridical research always begins with the premise of normative , which provides an explanation of normative , research results and expert opinion on the legal issues raised in the study . The conclusion that can be drawn from the legal consequences demise when the testator is still alive by the Book of the Law of Civil Law is null and void because it conflicts with Article 830 Book of the Law of Civil Law , granting inheritance can not be done while the testator is still alive. Keywords : Heritage, Heir, Life